Fast-Track Legislation: The Transformation of Law-Making Under Joko Widodo’s Administration - Huda, Ni’matul; Rishan, Idul; Pratiwi, Dian Kus (Yustisia, 2024)
Since the end of 2019, the President and the House of Representatives had performed different legislative functions. Since the Law on the Commission Eradication Commission was amended, legislation had dramatically been transformed.  Several laws have been passed and amended quickly. This study discusses three legal issues. First, the conceptual limitation of fast-track legislation in Indonesia. Second, the rationale behind fast-track legislation under Joko Widodo's administration. Third, the impact of fast-track legislation under Joko Widodo's administration. In this socio-legal study, a qualitative analysis is conducted. This study has identified that (1) fast-track legislation in Indonesia can only be adopted through Perpu with all its exemptions and exceptions; (2) the transformation of law-making under Joko Widodo's administration is associated with political pragmatism, political personalization, the elimination of the opposition, and cartel parties; and (3) the transformation of law-making under Joko Widodo's administration is detrimental to the future of Indonesia's democracy. The transformation has degraded the quality of deliberation in law-making. Besides, it does not adhere to law-making procedures, resulting in elitist and conservative laws.